The effect of sales promotion and service innovation toward ovo customer loyalty - Didi Tarmidi; Suci Rahmina Pratiwi (Enrichment : Journal of Management, 2023)
This study aims to see however the outline of sales promotion, service innovation, and customer loyalty, furthermore, as determine how the influence of sales promotion and service innovation on customer loyalty. The factors tested during this study are sales promotion and service innovation as independent variables, whereas customer loyalty could be a dependent variable. The analysis ways utilized in this study are descriptive and verification methods. The population in this study were those that used OVO services. The sampling technique used in this study is non-probability sampling and also the quantity of sample in this study is calculated by Bernoulli's formula so that the full variety is a hundred respondents. The analysis method in this study is using multiple regression analysis with the program of SPSS ver.25 for Windows. The results showed that Sales Promotion and Service Innovation affected OVO's customer loyalty. The number effect of sales promotion and service innovation toward customer loyalty is 37%.